Amelioration of physical and chemical properties of acidic soils with vinasse application - Hurtado, Alexander Calero [UNESP]; Traspadini, Edilaine Istéfani Franklin [UNESP]; De Sousa, Francisco Bruno Ferreira [UNESP]; Marchioro, Vinicius [UNESP]; Oliveira, Lorena Solar Silva; Santos, Laura Carvalho [UNESP]; Viciedo, Dilier Olivera; Calzada, Kolima Peña [UNESP]; Cazetta, Jáiro Osvaldo [UNESP] (Universidad Nacional Autonoma de Mexico, 2023)
The objective of this study was to investigate the acidic soil physical and chemical alteration associated to vinasse application under laboratory conditions. The experiment was distributed in a factorial scheme (5 × 3), in a completely randomized design, with four replicates. The beneficial effects of five vinasse doses (without vinasse [0, only water], 50, 100, 150, and 200 m3/ha) in enhancing the physical and chemical properties of three acidic soils: Oxisol (SO), Ultisol (SU), and Argisol (SA) were studied after 30 days of incubation. Soil samples were collected in the 0-20 cm depth layer to determine physical and chemical properties such as pH (CaCl2), total acidity (AT), exchangeable acidity (Al3+), base cations (K+, Ca2+, and Mg2+), sums of bases (SB), cations exchange capacity (CIC), base saturation index (V%), and saturation of potassium (K), calcium (Ca), magnesium (Mg), and aluminum (Al). Results indicated that vinasse application enhanced the physical and chemical properties of the studied soils, since pH, base cations, SB, CIC, V%, and saturation of K, Ca, and Mg were increased, while AT, Al3+, and Al saturation were decreased. The most important effects in the improvement of physical and chemical properties of acidic soils were observed with a dose of 200 m3/ha of vinasse. The findings of this study suggest that vinasse could be a low-cost effective strategy as an alternative source for balancing soil acidity and would be an appropriate option for minimizing environmental pollution.
MEJORAMIENTO DE LAS PROPIEDADES FÍSICAS Y QUÍMICAS DE LOS SUELOS ÁCIDOS CON LA APLICACIÓN DE VINAZA
Keywords: active acidity; base cations; cation exchangeable capacity; interchangeable acidity; waste